Revisión sistemática de la literatura sobre mejoramiento de las propiedades mecánicas del concreto adicionando fibras artificiales y naturales - Olivera Pérez, Yamalit Itamar; Guevara Saravia, Sandro Piero; Muñoz Pérez, Socrates Pedro (Ingeniería, 2022)
Context: Since structures are nowadays being affected due to the environment in which they are located, as well as by strong seismic movements, leading them in some cases to collapse. Method: A search of scientific articles for the period 2014-2021 was carried out in different databases. 56 research works that applied fibers were collected. To this effect, keywords such as hormigón reforzado, reinforced concrete, and mechanical properties of concrete were used. Results: The mechanical characteristics of concrete which should be prioritized for improvement should be compression resistance capacity, tensile strength, modulus of elasticity, durability properties such as resistance to chemical attack, shrinkage properties, permeability properties, and physical properties such as drying time, unit weight, erosion, and absorption. Conclusions: Among the artificial fibers most used by researchers, metallic fibers stand out. In the same way, among the natural fibers, banana, rice husk, and sugar cane bagasse stand out.